THE BOLOGNA DECLARATION AND ITS EFFECTS ON SWIMMING - Milomir Trivun (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The sample consisted of 24 tested students in 2009/10 academic year and 26 tested students in 2007/08 academic year. All of them were the second year students at the Faculty of Physical Education and Sport at the University in East Sarajevo and they were 22 years and ± 6 months old. There was done the results' comparison in the following variables: swimming the crawl at 100m and swimming the backstroke. The method of the study The results of descriptive statistics are shown in the measures of central tendencies: mean, minimum, maximum, standard deviation. Besides, the got results were subjected to the analysis by t-test and they referred to the small samples. The results of the research and the conclusions Applying the descriptive statistics and comparing results' success at swimming the crawl and backstroke at 100m there were got the results of the measures of central tendencies, this sample consisted of 26 tested students. There was applied t-test analysis at initial and final measuring of the swimming the crawl and backstroke. The results showed the statistically significant difference in swimming in relation to the population of 24 tested students in 2009/10 studying according to the Bologna Declaration.